The Problem of Human Identity in a Transboundary Sociocultural Space - Nadezhda S. Zimina (Transbaikal State University, 2021)
The socio-cultural cross-border is a space of interaction between cultures, which results in special social, cultural, socio-anthropological changes. The relevance of the research topic is determined by the fact that the socio-cultural space in which a person is located is constantly changing, exposed to outside influences, filled with new symbols, meanings, which is expressed in the transformation of the foundations of human life, cultural values, changes in his identity and the emergence of new personality types (“a marginal person”, “a transboundary person”), in the very ontological foundations of a person, changes in the boundaries of the space of his own identification, social relationships. The essence of the problem of human identity in the cross-border area is that, on the one hand, the person himself becomes cross-border, on the other hand, the cross-border area requires him to have a multidirectional orientation in self-identification. The aim of the work is to trace the influence of a multilayer transboundary space and the corresponding factors on a person’s identity, and to identify the types of personality and corresponding identity within the transboundary. The work uses dialectical, systemic, axiological, anthropological research methods, which together allowed a comprehensive approach to the analysis of the problem. As a result of the study of the influence of cross-border areas on human identity, some of its types were identified: cross-border, marginal, and transit ones. The work draws the following conclusions. A feature of identification in a transboundary space is its possible “transit” nature, which is determined by the search for new cultural forms close to a person and the constant transition in this regard from one form to another. Axiological involvement plays an important role in the identification of a person within a transboundary space, what he is guided by, what is important for him. Value orientations as the foundations of identity can be viewed through the prism of such positions as “our own-someone else’s”, “close-alien”, “I / we-they”, etc. The similarity of material and spiritual elements of culture, shared values serve as the basis for the formation of such meaningful characteristics of the transboundary sociocultural space as identity and self-awareness.